TRADE AND AFRICAN REGIONAL AGREEMENTS: A SPATIAL ECONOMETRIC APPROACH - Koch, Wilfried; Tientao, Aligui; Legros, Diègo (L'Actualité économique, 2019)
The purpose of this paper is to evaluate the impact of African regional blocs on African trade flows while allowing for spatial interdependence between trade flows. To this end, we derive a spatial gravity equation by removing the implicit assumption that trade flows between two trading partners are independent of what happens in the rest of the trading world. We estimate the border effects for five Sub-Saharan regional blocs (cemac, comesa, ecowas, sadc and waemu). We decompose the border effect into two components: a trade-boosting intra-bloc effect and a trade-reducing inter-bloc effect. Our findings show that trade agreements produce positive effects on intra-bloc trade flows and these effects are particularly prominent when the blocs are advanced in their integration process. In addition, the spatial interdependence between trade flows is reflected in a negative relationship as implied by the theoretical model, suggesting a natural measure of spatial competition.